2014
DOI: 10.3390/lubricants2020044
|View full text |Cite
|
Sign up to set email alerts
|

Graphite and Hybrid Nanomaterials as Lubricant Additives

Abstract: Lubricant additives, based on inorganic nanoparticles coated with organic outer layer, can reduce wear and increase load-carrying capacity of base oil remarkably, indicating the great potential of hybrid nanoparticles as anti-wear and extreme-pressure additives with excellent levels of performance. The organic part in the hybrid materials improves their flexibility and stability, while the inorganic part is responsible for hardness. The relationship between the design parameters of the organic coatings, such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
56
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(66 citation statements)
references
References 116 publications
0
56
0
4
Order By: Relevance
“…The term nanoadditive is commonly used for nanoparticles when they are used as an additive to conventional lubricants. Many studies have reported an effective role of nano-additives in lubricants in terms of improvement of anti-friction and anti-wear properties of materials [1][2][3]. These nano-additives are made up of nano-sized metals [4], metal-oxides [5] and diamond nanoparticles [6].…”
Section: Introductionmentioning
confidence: 99%
“…The term nanoadditive is commonly used for nanoparticles when they are used as an additive to conventional lubricants. Many studies have reported an effective role of nano-additives in lubricants in terms of improvement of anti-friction and anti-wear properties of materials [1][2][3]. These nano-additives are made up of nano-sized metals [4], metal-oxides [5] and diamond nanoparticles [6].…”
Section: Introductionmentioning
confidence: 99%
“…Conventional lubricant additives are generally thosecompounds containing sulfur, phosphor, or chlorine, among others [1][2][3] that play an important role in gear lubrication and cutting lubrication. However, the commercial applications of these kinds of additives are unsatisfactory because of the pungent odor, extreme corrosion, and the poor thermal stability [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it can be concluded that both methods (listed above) are classical and have their own defects (the addition of dispersant or usage of surfactant into base oil) for solving the oil solubility of TiO 2 nanoparticles. This claim is strengthened by the works of several researchers [3,[8][9][10][11]23,24,[36][37][38]. Therefore, the application process of the two classical methods was named the traditional process (TP).…”
Section: Introductionmentioning
confidence: 99%
“…Es importante mencionar que entre mas eficiente sea la dispersion de Nps en el aceite se obtendrá mayor poder lubricante con respecto a una concentración similar de Nps (Gu et al, 2013;Koshy et al, 2015;Song et al, 2012;Wan et al, 2015;Yang et al, 2012;Zhang et al, 2014). En esta investigación se estudió a nivel experimental la capacidad lubricante del aceite de ajonjolí extra virgen aditivado con nanopartículas de cobre en dispersión (DNpCu).…”
Section: Introductionunclassified